A new Cyrtodactylus Gray, 1827 (Squamata, Gekkonidae) from the Shan Hills and the biogeography of Bent-toed Geckos from eastern Myanmar - Grismer, L. Lee; Wood, Perry L. Jr.; Thura, Myint Kyaw; Quah, Evan S. H.; Grismer, Marta S.; Murdoch, Matthew L.; Espinoza, Robert E.; Lin, Aung (Zootaxa, 2018)
A phylogenetic taxonomic analysis indicates that a newly discovered population of Cyrtodactylus from the vicinity of Ywangan Town in the Shan Hills, Shan State, Myanmar is a new species (C. ywanganensis sp. nov.) and the earliest diverging member of the linnwayensis group within the previously defined Indochinese clade. The DIVALIKE+J model of a BioGeoBEARS biogeographic analysis indicates that the Indochinese clade evolved in the Shan Hills and Salween Basin of eastern Myanmar and dispersed into Indochina on at least three separate occasions from 18.6–13.4 mya. Once there, uplift of the Tenasserim Mountains and Thai Highlands created the intermedius group, the oldhami group, and C. tigroides of western and southern Thailand which form sister lineages to the linnwayensis group, yathepyanensis group, and the sinyineensis group, respectively, of eastern Myanmar. Diverging lineages within the Indochinese clade highlight the importance of the Thai Highlands and Tenasserim Mountains in that group’s evolution and speciation. The discovery of C. ywanganensis sp. nov. in karstic habitats in the Shan Hills continues to underscore the unrealized karst-associated herpetological diversity of this vast, relatively unexplored, upland region and the need for additional field studies.